A LOW-COST ADSORBENT COCONUT WASTE ASH ACTIVATED NaCl FOR METHYLENE BLUE REMOVAL - Pujiana, Nurliza; Yulianti, Eny; Rahmatulloh, Arief; Khalifah, Susi Nurul; Istighfarini, Vina Nurul (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2020)
Removal methylene blue from water using coconut waste ash activated by NaCl is studied in this paper. The characteristic of morphology and pore structure of coconut waste ash is analyzed using SEM, show that pores were formed after activation. XRF analysis revealed that the coconut waste ash before activation contains 20,19 % of Si. The effect of NaCl concentration on the adsorption behavior is investigated. The results show that the optimum concentration of NaCl to activating the coconut waste ash is 300 ppm. The adsorption capacity of coconut waste ash without activation, NaCl-activated coconut waste ash on 200 ppm, 300 ppm, and 400 ppm is 1.103 mg/g, 1.152 mg/g, 1.2102 mg/g, and 1.1109 mg/g respectively.